PEMANFAATAN INSTAGRAM SEBAGAI MEDIA INFORMASI PENGURUS HIMPUNAN PELAJAR MAHASISWA MASSENREMPULU KOMISARIAT UIN ALAUDDIN MAKASSAR - Harmin Hatta; Nurjayanti Nurjayanti; Muhammad Zia Ulhaq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Instagram has been present in all aspects of society's life without exception, this also happens to regional organizations originating from Massenrempulu, Enrekang Regency, the Massenrempulu Student Association (HPMM) UIN Alauddin Makassar Commissariat. Where the existence of Instagram as an information center can facilitate the performance of the HPMM Kom Management. UINAlauddin Makassar in publishing information and also as a medium to improve the organization's image. This research aims to find out and describe how Instagram is used and what the advantages and disadvantages are of using Instagram among HPMM Kom Management. UIN Alauddin Makassar as a source of information. Using Instagram is very helpful and beneficial for users because with Instagram we can find out about events or events that occur in society. Several advantages, specifically allowing HPMM Kom administrators. UIN Alauddin Makassar to be successful in publicizing activities via Instagram social media includes having good mastery of information technology. The ability to operate the Instagram platform and understand the various features and tools provided is a strong basis for compiling and presenting interesting content. The first inhibiting factor is the very limited facilities and equipment that are expected to support publication activities and the second is the classic problem related to the budget.